2018
DOI: 10.1080/1028415x.2018.1504428
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K2 protects PC12 cells against Aβ (1-42) and H2O2-induced apoptosis via p38 MAP kinase pathway

Abstract: Alzheimer's is an age-related disease with a hallmark of progressive loss of memory formation followed by a damage in the brain function due to the neural degeneration and extracellular beta-amyloid (Aβ) plaques accumulation. This study examines the protective effects of vitamin K2 on toxicity induced by (Aβ) and HO in PC12 cells as an appropriate model of Alzheimer's cell damage. PC12 cells pretreated with vitamin K2 (5-200 μM) for 4, 24 and 48 h, and exposed to either Aβ (25 µM) for 48 h or HO (150 µM) for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…Vitamin K 2 generates from the activity of intestinal bacteria or the conversion of dietary vitamin K 1 [ 7 ]. It has been reported that vitamin K 2 has a variety of biological functions, including anti-inflammation [ 8 ], antioxidant stress, antiapoptosis [ 9 ], stimulating autophagy [ 10 ] and serves as a mitochondrial electron carrier during oxidative respiration [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin K 2 generates from the activity of intestinal bacteria or the conversion of dietary vitamin K 1 [ 7 ]. It has been reported that vitamin K 2 has a variety of biological functions, including anti-inflammation [ 8 ], antioxidant stress, antiapoptosis [ 9 ], stimulating autophagy [ 10 ] and serves as a mitochondrial electron carrier during oxidative respiration [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the LDH assay showed that vitamin K2 significantly improved the cell membrane integrity which was found to be compromised by the treatment of streptozotocin and menadione. Such a neuroprotective role of vitamin K2 was also observed when differentiated rat pheochromocytoma PC12 cells were pre-treated with vitamin K2 and exposed to Aβ peptide and H 2 O 2 [28]. A similar cytoprotective effect of vitamin K2 was observed in astroglioma C6 cells, where it has been found to protect the C6 cells from Aβ-induced toxicity in a dose-dependent manner [29].…”
Section: Discussionmentioning
confidence: 57%
“…While post-treatment of vitamin K2 significantly reduced the ROS levels as indicated by the decreased fluorescence intensity of DCFH-DA, suggesting that vitamin K2 protected against streptozotocin-and menadione-induced toxicity by suppressing ROS accumulation. Similarly, vitamin K2 was found to be effective against Aβ [29] and H 2 O 2 [28] induced ROS generation. Increasing evidence reveals that increased ROS production is associated with damage to mitochondrial DNA and a decrease in mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…MK-4 improved energy production and rescued PINK1 mutation found in Parkinson’s disease [51]. More recently, research identified vitamin K2 protection of neurons via a novel mechanism involving P38 MAP kinase pathway [108]. Further to this, various K2 analogs have been found to be decisive in neuronal differentiation [109].…”
Section: Vitamin K2 In Health and Diseasementioning
confidence: 99%